2014
DOI: 10.1097/cji.0000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Blockade Enhances Antitumor Immunity of Intratumoral Injection of Immature Dendritic Cells into Irradiated Tumor in a Mouse Colon Cancer Model

Abstract: Dendritic cells (DCs)-based cancer immunotherapy has been used various strategies to inhibit immune suppressive mechanisms. CD25 antibodies and cyclophosphamide are well-studied immunomodulators through inhibition of regulatory T cells (Treg) and a blockade the immune-checkpoint molecule, cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) was recently targeted for immunomodulation. We used anti-CTLA-4 antibody, which is known to induce effective antitumor immunity by facilitating tumor-specific T-cell activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…Results from additional retrospective studies are consistent with these findings (213). In preclinical approaches with dendritic cell-based vaccines, CTLA-4 blockade enhanced efficacy compared to either therapy alone (214,215). When combined with appropriate adjuvants, long-peptide vaccines have induced clinical responses and T cell immunity (216,217).…”
Section: Wwwannualreviewsorg • Coinhibitory Pathways In Immunotherapysupporting
confidence: 73%
“…Results from additional retrospective studies are consistent with these findings (213). In preclinical approaches with dendritic cell-based vaccines, CTLA-4 blockade enhanced efficacy compared to either therapy alone (214,215). When combined with appropriate adjuvants, long-peptide vaccines have induced clinical responses and T cell immunity (216,217).…”
Section: Wwwannualreviewsorg • Coinhibitory Pathways In Immunotherapysupporting
confidence: 73%
“…In animal models, vaccination with peptideantigen-loaded DCs, in combination with systemic CTLA-4 blockade, demonstrated increased efficacy than either treatment alone [81][82][83]. Another study explored a different strategy, where immature DCs were used for in situ vaccination by injection directly into irradiated tumor, in combination with systemic CTLA-4 blockade [88], resulting in the inhibition of distant tumor growth and improved animal survival. A Phase I trial of combination of MART-1 peptidepulsed DC and tremelimumab has shown objective and durable tumor responses at the higher range of the expected response rate with either agent alone [89].…”
Section: Combining With Cancer Vaccine Therapymentioning
confidence: 99%
“…It is reasonable to hypothesize that radiotherapy combined with immunotherapy will lead to enhanced antitumor immune responses and improved clinical outcomes. Based on this theory, since the term "abscopal" has been proposed, dozens of preclinical studies and reviews have discussed this phenomenon and demonstrated the priming clinical outcomes of combinatorial treatment from radiotherapy and immunotherapy [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 96%